Training of the physical education professional to work in the children and adolescent health: an integrative review (Research, Society and Development, 2020)
Physical Education teachers can play a fundamental role in the quality of child and adolescent health, making initial and continuing training necessary to provide theoretical and practical knowledge to meet the recurring demands in this scenario. In order to consider the relevance of the proposed subject, the study aimed to investigate the scientific production in the Child and Adolescent Health area in the training of Physical Education teachers through an integrative literature review. Bibliographic searches were performed in the electronic databases LILACS, MEDLINE / PubMed, Web of Science and Scielo using combinations of Health Sciences Descriptors (DeCS). From the critical analysis of the selected articles, it can be highlighted, among other aspects, that there are implementation and improvement of public policies aimed at children (category 3) with the aim of improving the situation of children and adolescents through the performance of the Physical Education professional. Thus, it is important that teachers seek to strengthen the relationship between theory and pedagogical practice, as well as innovating, which is, experimenting with new models, strategies, methodologies, and contents, so that they can contribute to the integral education of children and adolescents.